Problem Perlindungan Hukum Terhadap Anak yang Bekerja (Analisis Data Profil Anak Indonesia 2021) - Yusron Munawir (Media of Law and Sharia, 2023)
Legal protection for working children in Indonesia needs special attention because currently there are still many working or employed children, so there is a risk of having children's constitutional rights guaranteed by the 1945 Constitution. Departing from the 2021 Indonesian child profile data, the author sees that there are problems with legal protection practices for children working in Indonesia. The research aims to determine the incompatibility between the legal protection practices of children working in Indonesia and the laws and regulations, as well as the factors that influence them. This research method is normative legal research with a statutory approach, which examines secondary data from the profile data of Indonesian children in 2021 which is analyzed with laws, concepts, and theories. The results of the study show that legal protection for children working in Indonesia in practice is still not by laws and regulations in several respects, namely 1) working children below the minimum age limit for work; 2) the duration of his working time exceeds the maximum limit; 3) the level of education is low; 4) child wages are far below the provincial minimum wage; 5) the majority of children work in the informal sector; 6) there is a legal vacuum regarding efforts to deal with children working outside of work relationships. Factors that influence the implementation of legal protection for working children in Indonesia are: 1) the substance of the law has not met the legal needs of child labor; 2) the legal structure is weak in monitoring and data collection; 3) needs support for adequate facilities and infrastructure to increase monitoring and outreach of data collection; 4) community factors related to economic problems, low awareness of education, knowledge about child labor, and community concern; 5) the legal culture views working children as a norm in society.